2007
DOI: 10.1152/ajpheart.01379.2006
|View full text |Cite
|
Sign up to set email alerts
|

Progressive troponin I loss impairs cardiac relaxation and causes heart failure in mice

Abstract: XP. Progressive troponin I loss impairs cardiac relaxation and causes heart failure in mice. Am J Physiol Heart Circ Physiol 293: H1273-H1281, 2007. First published May 25, 2007; doi:10.1152/ajpheart.01379.2006.-Cardiac troponin I (TnI) knockout mice exhibit a phenotype of sudden death at 17-18 days after birth due to a progressive loss of TnI. The objective of this study was to gain insight into the physiological consequences of TnI depletion and the cause of death in these mice. Cardiac function was monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Prolonged IRT and reversal of E/A wave ratio indicating impaired LV relaxation was recorded in cardiac troponin I (TnI) knockout (KO) mice and not in wild types. 17 Decreased and even reversal of E/A ratio was also shown in Tbx5 del/þ mice (model of Holt-Oram syndrome). This later model demonstrated reduced diastolic capabilities while systolic properties remained normal.…”
Section: Discussionmentioning
confidence: 94%
“…Prolonged IRT and reversal of E/A wave ratio indicating impaired LV relaxation was recorded in cardiac troponin I (TnI) knockout (KO) mice and not in wild types. 17 Decreased and even reversal of E/A ratio was also shown in Tbx5 del/þ mice (model of Holt-Oram syndrome). This later model demonstrated reduced diastolic capabilities while systolic properties remained normal.…”
Section: Discussionmentioning
confidence: 94%
“…The histological and functional measurement results clearly showed that TnI depletion altered both resting and active mechanical properties of ventricular myocytes and caused a lethal phenotype with shortened sarcomere length and a restricted ventricle due to a severe diastolic dysfunction [2,11]. The results also showed for the first time that expression of the adult cTnI isoform is not an essential component of the switch that terminates expression of the fetal ssTnI expression in the developing heart.…”
Section: A Phenotype Of Ctni Deficiency In Ctni-ko Micementioning
confidence: 89%
“…It is clinically important because troponin I can dramatically decrease in postinfarction left ventricular remodeled myocardium remote from the infarct zone [25] and the content of TnI in left ventricular myocardium may significantly decrease in older men with or without cardiac disease [26]. In addition, progressive troponin I loss can cause diastolic dysfunction and heart failure [27]. The similarities in regulation of TnI in lower and higher mammals and the down-regulation of slow skeletal TnI mRNA even in hypertrophied human heart imply tight genetic control of the expression of TnI gene in the heart.…”
Section: Discussionmentioning
confidence: 99%